Pengaruh Faktor Karakteristik Individu dan Budaya Organisasi terhadap Keterikatan Pegawai Generasi X dan Y - Fatimah, Hermin; Dharmawan, Arya Hadi; Sunarti, Euis; Affandi, M.Joko (Universitas Brawijaya, Indonesia, 2015)
The aim of this study is to examine the influence of individual characteristics andorganizational culture on employee engagement in generation X and Y. The study was conductedat the head office of a bank in Jakarta. This study is also intended to determinewhether there are perception differences between these two factors in generation X and Y.The data used in this study was collected through a questionnaire to 220 respondents consistingof 119 generation X respondents (59 men and 60 women) and 101 generation Yrespondents (44 men and 57 women). The comparison test (t test) and Structural EquationModeling (SEM) results show that there are no significant differences for the factors ofindividual characteristics between generations X and Y, because the bank has implementeda tight competency standard for recruitment such as hard worker, discipline, active in sociallife/organization for applicant who are acceptable. There is significant difference for organizationalculture, especially contributed by the result orientation and aggressiveness inwhich generation X is higher than generation Y. It is due to in this research the majorityrespondents for generation X are assistant director and have service time more than 15years compare to generation Y are assistant manager with service time below 7 years. Majorityof generation X are better understanding competitiveness culture in the bank that implementedperformance based culture. Both individual characteristics and organizational cultureare significantly affect employee engagement in generations X and Y. Therefore, therecruitment standard applied today still needs to continually utilize in order to minimize theindividual conflict between generation. In addition, organization needs to facilitate the staffto perform the value of organizational culture.